Treatment of severe Class II skeletal malocclusion in a hyperdivergent adult patient via hybrid clear aligner approach: A case report. (June 2023) - Palone, Mario; Brucculeri, L; Cremonini, F; Albertini, P; Lombardo, L
This case report describes the camouflage treatment of an adult patient with hyperdivergent facial pattern presenting with severe Class II skeletal malocclusion, through the use of a hybrid clear aligner approach, that relies on both a partial lingual fixed appliance and the continuous use of Class II elastics throughout therapy. After 11 months of treatment, the goals had been achieved, highlighting that the correct diagnostic framework, proper patient selection and careful digital planning of a compromise treatment can provide satisfactory aesthetic and functional outcomes.